2019
DOI: 10.1007/s11302-019-09675-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of purinergic receptors in hepatobiliary carcinoma in Pakistani population: an approach towards proinflammatory role of P2X4 and P2X7 receptors

Abstract: The primary malignancy of liver, known as hepatocellular carcinoma (HCC), comprises 9% of all hepatobiliary carcinomas. A steady rise has also been observed in adenocarcinoma (ADC) of the liver and ampullary carcinoma (AMC), ascending to 0.5% of gastrointestinal malignancies. Hepatobiliary carcinomas consist of 13% of all cancer occurrences worldwide. Purinergic receptor-based signaling holds the therapeutic potential based on its role in cell proliferation of several carcinomas. An altered ATP concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 41 publications
(44 reference statements)
2
34
0
Order By: Relevance
“…MEP1A has been explored as a prognostic marker for patients with HCC, especially early HCC, and it may play an important role in the progression of HCC by promoting migration and invasion of cancer cells ( 30 ). P2X4 receptor may be closely related to the downstream inflammatory process by activation of oxidative stress, inflammasome, and immune modulation for continuous cancer progression ( 31 ). Arun Asif et al demonstrated that increased RIPK2 activity leads to the activation of NF-κB, which up-regulates the proliferation, invasion, metastasis and anti-apoptosis of cancer cells ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…MEP1A has been explored as a prognostic marker for patients with HCC, especially early HCC, and it may play an important role in the progression of HCC by promoting migration and invasion of cancer cells ( 30 ). P2X4 receptor may be closely related to the downstream inflammatory process by activation of oxidative stress, inflammasome, and immune modulation for continuous cancer progression ( 31 ). Arun Asif et al demonstrated that increased RIPK2 activity leads to the activation of NF-κB, which up-regulates the proliferation, invasion, metastasis and anti-apoptosis of cancer cells ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an antibody directed against nfP2X7 also proved efficacious in reducing basal cell carcinoma growth in a phase I clinical trial on humans [83]. These data are of sure relevance to develop new P2X7-targeting therapies, also considering that an increasing number of studies report an association between P2X7 overexpression and bad prognosis or response to therapy in oncologic patients [42,65,72,[84][85][86][87]. The majority of these studies do not take into account known P2X7 variants, but some interesting progress was made in this field of research in last years that we cover in the present overview.…”
Section: Role Of Atp and P2x7 Receptor In Oncologymentioning
confidence: 99%
“…P2X4R are also expressed in many cancer types, including lung, colorectal, bladder cancer, leukaemia, brain tumour, and, most importantly to this study, PCa [ 19 ]. Functionally, most studies suggest that P2X4R positively associates with tumourigenesis [ 20 , 21 , 22 ]. However, whether and how P2X4R is involved in PCa progression remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%